Research of the Influence of Gear Fault on Time Varying Mesh Stiffness of Spur Gear Pair - Na'na Feng; Haimiao Wu (Jixie chuandong)
An analytical approach based on the simulation is proposed to quantify the time varying mesh stiffness （TVMS） of gear pair due to various gear tooth faults. Gear faults affecting transmission of gear pair are always accompanied by a stiffness reduction. TVMS is an important parameter in condition monitoring and description of dynamic characteristic of meshing gear pair. Potential energy method is one of the most widely used analytical methods to calculate TVMS. The potential energy method is used to study the influence of three fault conditions on the gear meshing stiffness， including cracked gear， broken tooth and tooth surface spalling. The results indicate that due to presence of gear faults， the TVMS reduces which affect the vibration response of spur gear pair.